Manajemen Kepemimpinan dalam Pendidikan Kontemporer melalui Perspektif Islam - Hairul Puadi (LPPI Universitas Al-Qolam Malang, 2025)
The Industrial Revolution 4.0 has transformed the global landscape. In these times, leadership in Islamic education faces various complex challenges. This description demonstrates the ability of Islamic educational leadership to realize its lofty ideals as “leadership management” in Islamic education. The definition of leadership in education can be formulated as follows: “Educational leadership is a series of abilities of a person in the educational process that is effective and efficient in achieving goals.” Based on its implementation, official leadership is divided into: (1) Autocratic Leadership Type. (2) Pseudo-Democratic Leadership Type. (3) Laizzez Faire Leadership Type. (4) Democratic Leadership Type. As for the definition of leadership in Islam, in Arabic it is called